(untitled) (Simbiótica. Revista Eletrônica, 2022)
An investigation into the images on the Herberto Helder’s writing. The color red. Flesh. Approaching the work of the Portuguese-Brazilian artist Artur Barrio (1979) broadens the perception of this herbertian universe. Other manifestations of the images appear in this work of art encounters. Painting and writing approach each other through the perspective of the red color. Van Gogh and Helder are put side by side in the enigma of the visible. The color red also signifies that which is unspeakable in art and a relation of Tarantino’s cinema highlights the incarnate image of the poet. A dreamlike mood illuminates the incomprehensible and diabolical in shades of a mutant red. Keyword: Image; Red; Poetry; Art.